The Influence of Work Discipline on the Work Productivity of Tahu SME (Small and Medium Enterprise) Employees, Gadingrejo District, Pringsewu Regency - Irine, Brigita; Barusman, Muhammad Yusuf Sulfarano (PT FORMOSA CENDEKIA GLOBAL, 2024)
The current study aims to investigate in depth the relationship between employee work discipline and work productivity levels in the Tofu MSMEs of Gadingrejo sub-district, Pringsewu district. A quantitative approach was chosen as the research method, with data collected directly from employees through questionnaires and observations, covering a total population of 30 employees. The data collected was then analyzed using multiple linear regression models. The results of the analysis reveal that the effect of work discipline on the work productivity of tofu UMKM employees, the work discipline variable has a significant effect on employee work productivity. It is hoped that the findings of this study can contribute to improving work discipline in Tofu MSMEs in Gadingrejo District, Pringsewu Regency towards work productivity in employees, by further considering the shortcomings of developing employee performance. Of course it helps Tofu MSMEs improve Employee Productivity and Work Discipline that has been higher than before.